Mobile intervention for used clothing management with geolocation / Muhammad Haziq Anuar and Siti Sarah Md Ilyas - Anuar, Muhammad Haziq; Md Ilyas, Siti Sarah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Clothes can be one of the causes of the environmental pollution. This is because the clothes were thrown away in the landfills when it is become worn and unwearable. To overcome this problem, an initiative to develop Mobile Intervention for Used Clothing Management with Geolocation. This project is an initiative to be a donation medium for used clothing that people want to donate. Furthermore, this project also implements the Geolocation technology, which purposely to find the collection center for used clothing donation. The System Development Life Cycle (SDLC) was implemented in methodology of developing this application with Waterfall methodology. For a better development, the User Experience Testing (UXT) was conducted with 31 participants to ensure that the application is parallel with the requirements and achieve its goals. Based on the results, the participants give good comments and satisfied with the ability of the developed mobile application. In conclusion, this application will give many benefits and advantages for its target user, especially people who want to make donations based on used clothing material.